'You Can't Dismiss that as Being Less Happy, You See it is Different'. Sexual Counselling in 1950s England. (13th April 2019) - Rusterholz, Caroline
Abstract: This article uses the audio recordings of sexual counselling sessions carried out by Dr Joan Malleson, a birth control activist and committed family planning doctor in the early 1950s, which are held at the Wellcome Library in London as a case study to explore the ways Malleson and the patients mobilised emotions for respectively managing sexual problems and expressing what they understood as constituting a 'good sexuality' in postwar Britain. The article contains two interrelated arguments. First, it argues that Malleson used a psychological framework to inform her clinical work. She resorted to an emotion-based therapy that linked sexual difficulties with unconscious, repressed feelings rooted in past events. In so doing, Malleson actively helped to produce a new form of sexual subjectivity where individuals were encouraged to express their feelings and emotions, breaking with the traditional culture of emotional control and restraint that characterized British society up until the fifties. Second, I argue that not only Malleson but also her patients relied on emotions. The performance of mainly negative emotions reveals what they perceived as the 'normal' and sexual 'ideal'. Sexual therapy sessions reflected the seemingly changing nature of the self towards a more emotionally aware and open one that adopted both the language of emotions and that of popular psychology to articulate his or her sexual difficulties.